2020
DOI: 10.3390/cancers12030592
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Cancer with Radiographically Occult Metastatic Disease: Biology, Challenges, and Diagnostic Approaches

Abstract: Gastric adenocarcinoma is an aggressive cancer that demonstrates heterogeneous biology depending on patient ethnicity, tumor location, tumor type, and genetic profile. It remains the third leading cause of cancer deaths worldwide and was estimated to result in 782,000 deaths in 2018. Challenges exist in accurately assessing the disease burden, as available radiological staging often underestimates metastatic disease. This diagnostic handicap, along with the poor understanding of the heterogeneous biology of ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 79 publications
1
2
0
Order By: Relevance
“…Although the location of the primary tumour in the studies included did not show any distinct distribution pattern, most of the lesions arise from non-cardia areas, which corresponds to literature by Rijken et al [ 44 ] and Sanjeevaiah et al [ 46 ] It is frequently reported that signet ring cell or diffuse type tumours have a greater risk of peritoneal metastases but the majority of cases seen in the studies are adenocarcinomas[ 44 , 47 , 48 ]. This may be attributed to the vast majority of gastric cancers being adenocarcinomas or intestinal types[ 49 , 50 ].…”
Section: Discussionsupporting
confidence: 75%
“…Although the location of the primary tumour in the studies included did not show any distinct distribution pattern, most of the lesions arise from non-cardia areas, which corresponds to literature by Rijken et al [ 44 ] and Sanjeevaiah et al [ 46 ] It is frequently reported that signet ring cell or diffuse type tumours have a greater risk of peritoneal metastases but the majority of cases seen in the studies are adenocarcinomas[ 44 , 47 , 48 ]. This may be attributed to the vast majority of gastric cancers being adenocarcinomas or intestinal types[ 49 , 50 ].…”
Section: Discussionsupporting
confidence: 75%
“…A German study showed that even 55% of cancerous-infiltrated LN remain smaller than 5 mm [26], which implies high possibility of false-negative and false-positive results. Limitations are related to poor visualisation of nodal engagement [21,27], nodal location dependency and sensitivity rate of 44.4% [22]. Moreover, in up to 30% of negative CT scans, endoscopic ultrasound (EUS) reveals nodal involvement [27,28].…”
Section: Computed Tomographymentioning
confidence: 99%
“…Limitations are related to poor visualisation of nodal engagement [21,27], nodal location dependency and sensitivity rate of 44.4% [22]. Moreover, in up to 30% of negative CT scans, endoscopic ultrasound (EUS) reveals nodal involvement [27,28]. Another restriction is associated with ambiguous restaging before potential gastrectomy.…”
Section: Computed Tomographymentioning
confidence: 99%